Target and suspect screening for biocides in drinking water resources of Honduras. Issue 1 (21st February 2022) - Sherman, Anya; Mejia, Walter Alejandro Guardado; Padilla, Natasha Ramos; Carpenter, Corey M. G.; Rich, Stephanie L.; Moncada, Erika Tenorio; Helbling, Damian E.
Abstract: The objective of this research was to explore biocide occurrence in drinking water resources of Honduras. We collected 46 samples from seven drinking water treatment plants (DWTPs) in Honduras during eight sampling events between October 2018 and August 2019. We used high-resolution mass spectrometry to quantify the concentrations of 55 target biocides and estimate the abundance of four priority suspect biocides and five additional high-abundance biocides. We measured 30 of the target biocides, one of the priority suspect biocides, and all five of the high-abundance biocides in at least one of the samples. No correlation was observed between the overall extent of agriculture and biocide occurrence. However, bean production was strongly and significantly correlated with the biocide mixture complexity, as well as with concentrations of aminobenzimidazole and abscisic acid. Biocide mixture complexity was higher during the rainy season than during the dry season, but biocide concentrations were lower during the rainy season. Finally, we found that existing DWTPs are not consistently effective at removing the target biocides. These data represent the first known broad survey of bioicides in drinking water resources of Honduras and demonstrate the need for further study to better understand and manage biocide occurrence. HIGHLIGHTS: Agricultural biocides are measured in water samples from Honduras. Thirty different target biocides are measured in at least one sample. The extent of biocide occurrence is not associated with the extent of land used for agriculture. More biocides measured in water samples from the rainy season but at lower concentrations. Existing drinking water treatment practices have little effect on biocide concentration. Graphical Abstract